Simulation of elastic-dissipative connection of multi-axle block-modular agricultural tractor modules - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Булгаков, Владимир Михайлович; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Ivanovs, Semjons; Melnyk, Viktor (My University, 2021)
Creation of a tractor according to a modular scheme, by combining the power and the technological modules into a single multi-axle power unit can essentially improve its traction and coupling properties. Research in possibilities how to increase smooth running of a multi-axle block-modular tractor by damping its vertical oscillations due to throttling of the hydraulic system of the rear suspension mechanism of the power module is an urgent task. Synthesis of the connection parameters of the modules of a multi-axle block-modular agricultural tractor was effected by simulating the conditions of its operation on a PC. The model of functioning of a hydraulic suspension mechanism of the power module of a multi-axle block-modular agricultural tractor with a sudden narrowing of the main hydraulic line of the main hydraulic cylinder, as a throttling system, was represented by a combination of elastic and dissipative elements. Creation of a dynamic system with viscoelastic damping by throttling the hydraulic system of the suspension mechanism of the power module allows damping the oscillations of block-modular units in the vertical plane in a wider frequency band (0… 16 s-1). In addition, dispersion of the mutual vertical oscillations of the power and the technological modules during the agricultural operations is reduced by more than 3 times, and the allowed vibration load of the operator is ensured.
Keywords: block tractor; damping; oscillations; module